Development and testing of a device to detect trigger points, and local twitch responses in dry needling intervention - Manoj Kumar Sharma; Sarika Chaudhary; Hardika Sood (MethodsX, 2025)
Trigger point dry needling (TrpDN) has emerged as a promising intervention for the treatment of myofascial pain. This involves insertion of a sterile filament needle directly into the trigger point (Trp), with the aim of eliciting a local twitch response (LTR). This sudden, involuntary contraction of the muscle fibers confirms the breakdown and success of TrpDN intervention. Not all LTRs are perceptible through visual observation or tactile sensation during the intervention. In search of noticeable LTR, clinicians perform Hong's technique (back-and-forth movements of needle in muscle). This results in muscle damage and causes pain and discomfort thereby limiting functional movements of patients. One important factor in the diagnosis and post intervention follow-up of TrpDN is the pain pressure threshold (PPT). Currently most of the clinicians use thumb pressure and subjective scales for confirming trigger points. These methods can introduce biasness due to its reliance on subjective factors. • In this present study, an effort has been made to assemble a device to overcome the challenges faced during assessment and treatment of trigger points. • This device can provide audiovisual feedback for LTR and can measure PPT.